Theoretical and Applied Aspects of Ensuring Financial Inclusion as an Integral Component of Banking Sector Reformation - Iermak, Valerij (Pressing Problems of Public Administration, 2024)
This paper addresses the issue of ensuring financial inclusion as a component of banking sector reform. The aim of the study is to provide a theoretical justification for the growing role of financial inclusion in the context of banking sector reform and to develop relevant recommendations for improving regulatory policy regarding banking sector reform in Ukraine. This necessitated the formulation and resolution of four research objectives: examining the essence and components of financial inclusion; analyzing the current state of banking services accessibility in Ukraine; identifying the main problems and obstacles to the inclusivity of banking services; developing proposals to increase the level of banking services inclusivity.The paper systematizes scientific approaches to the definition of «financial inclusion» and proposes its own interpretation in the context of the banking sector. Statistical data on the level of banking services accessibility in Ukraine during the pre-war period and under the legal regime of martial law are examined. The main problems and obstacles to the inclusivity of banking services are identified, and tools and strategies for developing financial inclusion in the course of banking sector reform are proposed. The conclusion is drawn that financial inclusion in Ukraine demonstrates positive dynamics, but requires further efforts to fully bridge the gap in access to financial services and ensure equal conditions for all segments of the population.The article makes a key conclusion that the introduction of digital financial education and expanding access to financial services in remote areas are crucial steps to increase financial inclusion in Ukraine. These measures will not only enhance financial literacy and access to financial services but also create a solid foundation for the country’s sustainable economic development in the future. Both proposals are aimed at utilizing technological innovations to overcome existing barriers to financial inclusion, taking into account Ukraine’s specific conditions. Their implementation will require close cooperation between the government, the National Bank of Ukraine, the financial sector, and technology companies, but the potential benefits for the economy and society are significant.